Everyone is Teacher Here: Alternatif Metode Pembelajaran Efektif untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Yunanda Putri Ariska; B. Fitri Rahmawati; Muhammad Shulhan Hadi (Universitas Hamzanwadi, 2023)
This research aims to determine the effectiveness of the Everyone Is A Teacher Here learning method on students' critical thinking abilities in the history subject class XI MA Mu'allimat NWDI Pancor. This research uses a quantitative approach with experimental methods. The type of experiment used is quasi-experimental because the researcher cannot control other variables that might have an influence on the research. The experimental design used was a posttest only control group design, namely a design that did not conduct a pretest on research subjects. This was done considering that the learning outcomes between the experimental and control groups were relatively the same. Data collection uses observation to obtain data regarding the implementation of learning using the everyone is teacher here method and students' critical thinking abilities. Data was obtained using an instrument in the form of an observation sheet. Data analysis uses inferential statistical analysis, namely using Mann Whitney nonparametric statistics because the data is not normally distributed. Testing was carried out using SPSS 25.0. The results of hypothesis testing show that the Everyone Is A Teacher Here learning method is effective in improving students' critical thinking skills with a significance value (2-tailed) of 0.000 <0.05, which shows that there is a significant difference between the average results of the experimental class and the control class.